Pengaruh Lingkungan Belajar Dan Pola Asuh Orang Tua Terhadap Prestasi Belajar Siswa Kelas Tinggi SD Negeri Munggung 1 Tahun Ajaran 2015/2016 - Wulandari, Novita; , Sri Hartini, S.H., M. Pd (2016)
Education is a conscious and deliberate effort to create an atmosphere of learning and the learning process. Learning is the key to one's success. The purpose of this study include the know: 1) the influence of the learning environment on student achievement of high grade at SDN Munggung first academic year 2015 / 2016.2) influence parenting parents on student achievement of high grade at SDN Munggung first academic year 2015 / 2016.3) how much influence the learning environment and parenting parents on student achievement of high grade at SDN Munggung I 2015/2016 academic year. This type of research is based on a quantitative approach ith type of research Quasi Experiment. The analysis technique used is double linear regression, t-test, f. based on analysis of data: 1) the equation obtained regression coefficient is Y = 48.032 + 0.079 (X1) + 0.207 (X2) .2) t-test learning environment to learning achievement thitung 2.315> 2.034 ttable, learning environment positive effect on learning achievement. 3) parents' parenting positive effect on the interpretation of study, it is based on the results of the t test tcount 4.182> ttabel 2,034.4) F-test significance value 0.000 <0.05, meaning the learning environment and parenting parents together positive effect on achievement high grade students of SD Negeri Munggung 1 academic year 2015/2016.